CARMA3: A potential therapeutic target in non-cancer diseases - Gui, Zhen; Zhang, Yan; Zhang, Aihua; Xia, Weiwei; Jia, Zhanjun (Frontiers in Immunology, 2022)
Caspase recruitment domain and membrane-associated guanylate kinase-like protein 3 (CARMA3) is a scaffold protein widely expressed in non-hematopoietic cells. It is encoded by the caspase recruitment domain protein 10 (CARD10) gene. CARMA3 can form a CARMA3-BCL10-MALT1 complex by recruiting B cell lymphoma 10 (BCL10) and mucosa-​associated lymphoid tissue lymphoma translocation protein 1 (MALT1), thereby activating nuclear factor-​κB (NF-κB), a key transcription factor that involves in various biological responses. CARMA3 mediates different receptors-dependent signaling pathways, including G protein-coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs). Inappropriate expression and activation of GPCRs and/or RTKs/CARMA3 signaling lead to the pathogenesis of human diseases. Emerging studies have reported that CARMA3 mediates the development of various types of cancers. Moreover, CARMA3 and its partners participate in human non-cancer diseases, including atherogenesis, abdominal aortic aneurysm, asthma, pulmonary fibrosis, liver fibrosis, insulin resistance, inflammatory bowel disease, and psoriasis. Here we provide a review on its structure, regulation, and molecular function, and further highlight recent findings in human non-cancerous diseases, which will provide a novel therapeutic target.